2021
DOI: 10.1055/s-0040-1717133
|View full text |Cite
|
Sign up to set email alerts
|

Successful Homoeopathic Treatment of Phyllodes Tumour: A Case Study

Abstract: Phyllodes tumours (PTs) of the breast are rare biphasic fibroepithelial neoplasm. They have potentiality to recur and metastasise. Majority of them follow a benign clinical course. We have treated one patient suffering from PT at the out-patient department of Sri Ram Medical & Homoeopathic Research Centre, Gorakhpur, India. After detailed case taking and repertorisation, first Conium maculatum and later on Phytolacca decandra and Calcarea fluorica were prescribed on the basis of individualisation to treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Based on a holistic therapeutic strategy and patient-centered care, the homeopathic system of medicine can deliver both costeffective and complete medical care. 6 Randomized controlled trials (RCTs), 7,8 observational studies [9][10][11] and case reports 12,13 on the management of the different clinical conditions manifested in the case under study have shown varying success.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a holistic therapeutic strategy and patient-centered care, the homeopathic system of medicine can deliver both costeffective and complete medical care. 6 Randomized controlled trials (RCTs), 7,8 observational studies [9][10][11] and case reports 12,13 on the management of the different clinical conditions manifested in the case under study have shown varying success.…”
Section: Introductionmentioning
confidence: 99%